Exploring multilevel determinants of stillbirth: a comprehensive analysis across sub-Saharan African countries - Oluwabunmi Ogungbe; Khadijat Adeleye; Yvette Yeboah-Kordieh; Ashley Gresh; Favorite Iradukunda (BMJ Open)
Background Stillbirths and associated outcomes remain a significant concern in sub-Saharan Africa (SSA), with approximately 41% of global stillbirths.Design Our cross-sectional analysis included a weighted sample of women aged 15–49 years who had given birth or experienced stillbirth.Setting Sub-Saharan African Countries.The main outcome measures Determinants of stillbirth among women in 29 SSA countries.Result Among a sample of 197 328, stillbirth prevalence was 8.4/1000 live births. Among individual-level factors, the risk increased with age. Higher maternal educational levels were significantly associated with decreased stillbirth risk (aOR=0.62, 95%CI: 0.44 to 0.89, higher versus no education). Single women had significantly lower odds of stillbirth compared with those who no longer lived together or were separated from their partners (aOR=0.38, 95%CI: 0.25 to 0.60). Contextually, women with a job had an increased risk compared with women without a job (aOR=1.19, 95%CI: 1.06 to 1.34), and living in a rural residential area was a significant factor (aOR=1.30, 95%CI: 1.13 to 1.50).Conclusion The complex interplay between individual-level and contextual factors continues to influence stillbirth outcomes in SSA. Cross-sector integrative care approaches to maternal and neonatal health are needed to address the multifaceted determinants of stillbirths.